1990
DOI: 10.1029/jb095ib10p15853
|View full text |Cite
|
Sign up to set email alerts
|

Reversals of the orthoenstatite‐clinoenstatite transition at high pressures and high temperatures

Abstract: The MgSiO3 orthoenstatite‐clinoenstatite (OEn‐CEn) phase boundary has been reversed between pressures of 70 and 110 kbar and temperatures of 900°C and 1700°C with a split‐sphere anvil apparatus (USSA‐2000). Starting materials contained PbO‐PbF2 (1∶1) flux to promote equilibration of the charges and eliminate a potential effect of deviatoric stresses on the phase boundary. The phase boundary separating orthoenstatite from clinoenstatite at high pressures and temperatures can be described by the equation P (kbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(72 citation statements)
references
References 16 publications
4
68
0
Order By: Relevance
“…The EOS fitted parameters, H o f and S o for orthoenstatite and low-pressure clinoenstatite are from Fabrichnaya and Kuskov (1994), Skinner (1966), Pacalo and Gasparik (1990), Angel and Hugh-Jones (1994), Yang and Ghose (1994), Hugh-Jones (1997), Jackson et al (1999), and Shinmei et al (1999). Using K S = 107.7 GPa and K = 5 for orthoenstatite, the difference between experimental (Angel and Hugh-Jones 1994) and calculated volumes for orthoenstatite at pressures up to 8.5 GPa is no more than 0.1-0.3%; see also Jackson et al (1999).…”
Section: Mg 2 Sio 4 (Forsterite) Fe 2 Sio 4 (Fayalite)mentioning
confidence: 99%
“…The EOS fitted parameters, H o f and S o for orthoenstatite and low-pressure clinoenstatite are from Fabrichnaya and Kuskov (1994), Skinner (1966), Pacalo and Gasparik (1990), Angel and Hugh-Jones (1994), Yang and Ghose (1994), Hugh-Jones (1997), Jackson et al (1999), and Shinmei et al (1999). Using K S = 107.7 GPa and K = 5 for orthoenstatite, the difference between experimental (Angel and Hugh-Jones 1994) and calculated volumes for orthoenstatite at pressures up to 8.5 GPa is no more than 0.1-0.3%; see also Jackson et al (1999).…”
Section: Mg 2 Sio 4 (Forsterite) Fe 2 Sio 4 (Fayalite)mentioning
confidence: 99%
“…In addition, the chemistry of coexisting phases is dependent on pressure and temperature. Pacalo and Gasparik [1990] and Kanzaki [1991] have shown that pure enstatite transforms from the orthorhombic structure to the high clinoenstatite structure near 8 GPa and 1000øC. At still higher pressure, the components of pyroxene dissolve into the majorite garnet phase.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk TiO 2 contents of individual olivine grains from both localities were analyzed with a comprehensive grid of 5-, 10-, and 20-m diameter electron beams at 15 kV accelerating voltage, 15 to 100 nA sample current, and counting times of 200 to 2000 seconds (Table 1). All analyzed grains yielded bulk TiO 2 contents of hundreds of parts per million (15), including three inclusion-rich grains, "ol-1," "ol-2," and "ol-3" from sample 3-73-AA, loaned to us by L. Dobrzhinetskaya. To pursue this factor of 10 or more disparity between our measured TiO 2 contents and their calculated TiO 2 contents, we isolated an area of 225 ϫ 575 m from grain "ol-1" to analyze in greater detail (Fig.…”
mentioning
confidence: 99%
“…To our knowledge, this is the only occurrence of clinoenstatite in diopside recorded. A possible explanation would be exsolution of high-pressure clinoenstatite from diopside at very high pressures [P Ͼ 8 GPa for a normal mantle geotherm (15)] and inhibition of transformation to orthoenstatite during subsequent pressure reduction because of sluggish nucleation kinetics or coherency stresses between the lamellae and diopside host. The high-pressure polymorph of clinoenstatite cannot be preserved because at lower pressures it undergoes a nonquenchable second-order transformation to the low pressure form (16).…”
mentioning
confidence: 99%